2012
DOI: 10.2217/rme.12.51
|View full text |Cite
|
Sign up to set email alerts
|

Key Anticipated Regulatory Issues for Clinical Use of Human Induced Pluripotent Stem Cells

Abstract: The production of human induced pluripotent stem cells (hiPSCs) has greatly expanded the realm of possible stem cell-based regenerative medicine therapies and has particularly exciting potential for autologous therapies. However, future therapies based on hiPSCs will first have to address not only similar regulatory issues as those facing human embryonic stem cells with the US FDA and international regulatory agencies, but also hiPSCs have raised unique concerns as well. While the first possible clinical use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Regulatory issues related to the use of human iPSC products are currently being evaluated by the Center for Biologics Evaluation and Research at the United States Food and Drug Administration (97). According to published requirements, evaluation of iPSC-derived products for patient treatments includes preclinical testing to examine safety, feasibility, and efficacy.…”
Section: Overview Of Preclinical Testing Requirements For Ipsc Productsmentioning
confidence: 99%
“…Regulatory issues related to the use of human iPSC products are currently being evaluated by the Center for Biologics Evaluation and Research at the United States Food and Drug Administration (97). According to published requirements, evaluation of iPSC-derived products for patient treatments includes preclinical testing to examine safety, feasibility, and efficacy.…”
Section: Overview Of Preclinical Testing Requirements For Ipsc Productsmentioning
confidence: 99%
“…Despite this promise, the past decade has also shown that translating the potential of stem cell therapy into actual practice is not easy, and many barriers, including immunorejection (22, 129), teratogenesis (106), regulatory (107) and ethical issues (46), still need to be overcome before such strategies become commonplace in the clinic. Thus, discussions of therapeutic efficacy to restore functionality to irradiated tissues are provided along with the caveats associated with such treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The issues regarding the cell and gene therapy in every country are governed by its sovereign regulatory body. In the United States, the human iPSC products are regulated by Centre for Biologics Evaluation and Research at the United States Food and Drug Administration (USFDA) . Before proceeding with the clinical trials, the iPSC‐derived products are subjected to preclinical testing that requires extensive examination of safety, feasibility and efficacy .…”
Section: Recent Developments In Safe Clinical Productsmentioning
confidence: 99%
“…Facioscapulohumeral muscular dystrophy (FSHD) [184] Limb-girdle muscular dystrophy (LGMD) [185] Myotonic dystrophy type 1 (MyD1) [186] Marfan syndrome (MFS) [187] Fibrodysplsia ossificans progressiva (FOP) [188] Lung disorder Cystic fibrosis (CF) [189] Pulmonary alveolar proteinosis (PAP) [190] Emphysema (EP) [191] Dermatological Disorder Recessive dystrophic epidermolysis bullosa (RDEB) [192,193] Scleroderma (SC) [191] Focal dermal hypoplasia (FDH) [194] Hermansky-Pudlak syndrome (HPS) [195] Chediak-Higashi syndrome (CHS) [195] Cancer Breast cancer (BC) [196] Opthalmological disorder Retinitis pigmentosa (RP) [53,197,198] Gyrate atrophy (GA) [199] Best disease (BD) [200] Cataract (Cat) [201] Ectrodactyly-ectodermal dysplasia-cleft syndrome (EEC) [202] Nephrology End stage renal disease (ESRD) [203] Aneuploidy Turner syndrome (TS) [204] Warkany syndrome (WKS) [204] Patau syndrome (PS) [204] Emanuel syndrome (ES) [204] Klinefelter's syndrome (KS) [205] Down's syndrome [125] 1580 States, the human iPSC products are regulated by Centre for Biologics Evaluation and Research at the United States Food and Drug Administration (USFDA) [214]. Before proceeding with the clinical trials, the iPSC-derived products are subjected to preclinical testing that requires extensive examination of safety, feasibility and efficacy [215].…”
Section: Disease Modelling Referencesmentioning
confidence: 99%